Development of E-Module Based Physics Test Instrument: Multiple Choice Test - Ayu Sukma, Melani Dyah; Nugroho, Kuncoro Asih; Setiaji, Bayu (Universitas Islam Negeri Ar-Raniry, 2025)
The purpose of this study was to develop a question instrument and describe the validity of reliability, and item analysis. The research design used in developing the instrument is RnD with the 4D method. Based on the results of the analysis and discussion, it can be concluded that the results of expert validation meet the valid criteria. The empirical validity obtained states that it meets the validity criteria with a good category. The results of the reliability test on the product show that the test instrument is quite reliable. The results of the item analysis stated that the instrument was in the category of good difficulty level. In the analysis of item discrimination, there are 15 categories of questions that are feasible to maintain. In the analysis of item distractors, there are 15 questions with distractors that are accepted because they are good enough and there are 5 questions whose distractors are revised. This research is useful for knowing how the level of quality and effectiveness of the development of test instruments.